Coach-athlete relationship, team cohesion and motivation in Brazilian youth athletes: a cluster analysis - Gabriel Lucas Morais Freire; Andressa Ribeiro Contreira; José Fernando Vila Nova De Moraes; Daniel Vicentini De Oliveira; Lenamar Fiorese; José Roberto Andrade Do Nascimento Junior (Termedia Publishing House, 2022)
Purpose This study investigated whether coach-athlete relationship development through sport was influenced by demographic factors, team cohesion, and motivation variables in Brazilian youth sport participants. Methods The research involved 301 young athletes (136 boys and 165 girls) participating in the final phase of the School Games. They were aged 14-17 years (mean: 16.03 ± 0.83 years). The survey used assessed demographic variables, the Coach-Athlete Relationship Questionnaire, the Sport Motivation Scale, and the Youth Sport Environment Questionnaire. The data were investigated with a cluster analysis, chi-squared test, and multivariate analysis of variance ( p < 0.05). Results The study revealed more female participants in the high coach relationship cluster ( p = 0.010), as well as a stronger association of futsal and handball with high coach-athlete relationship quality, and of basketball with low coach-athlete relationship quality ( p = 0.002). When compared with the low coach relationship cluster, youth sport participants in the high coach relationship cluster presented higher scores for social cohesion ( p = 0.001), task cohesion ( p = 0.001), and autonomous motivation regulations ( p : 0.003-0.001). Conclusions Such findings suggest that coaches should seek to encourage group cohesion for both task and social cohesion, thus motivating athletes to meet the demands of the sporting context.